Ancaman Pidana Bagi Intellectuel Dader Black Campaign: Studi Putusan Nomor 17/Pid.Sus/2014/PN.Bul - Achmad, Rafli Fadilah (Jurnal Hukum & Pembangunan, 2018)
Black Campaign is a prohibited campaign method conducted based on agitation, slander, pit fighting, lies or hoaxes. The vast growth of social media platform has emerged as a distinct challenge in Black Campaign eradication. The popular form of Black Campaign nowadays constitutes reality bending photo and video editing, candidate discussing a fake issue, whatsapp broadcasting, hoax news creation and distribution, and fake polls. As such, Black Campaign law enforcement in the end that focuses not only on the strafbaarfeit element but also narrowing to the intellectuele dader element. Black Campaign regulation has been administrated in several regulation concerning Election in national scale and Regional Election in local scale, which was principally regulated in Criminal Law Code, Law Concerning. Electronic Information and Transactions, Law concerning Governor, Regent and Mayor Election, and Law concerning General Election. This research is also supplemented by case decision study on case No. 17/Pid.Sus/2014/PN.Bul.